A Simplicial Complex is Uniquely Determined by Its Set of Discrete Morse Functions - Capitelli, Nicolás Ariel (2017)
We prove that a connected simplicial complex is uniquely determined by its complex of discrete Morse functions. This settles a question raised by Chari and Joswig. In the 1-dimensional case, this implies that the complex of rooted forests of a connected graph G completely determines G.